IL-6-induced pathophysiology during pre-eclampsia: potential therapeutic role for magnesium sulfate? - LaMarca, Babbette (2011)
Pre-eclampsia is defined as new onset hypertension with proteinuria during pregnancy. Pre-eclampsia is also characterized by endothelial cell activation and dysfunction and intrauterine growth restriction. Preeclamptic women display a chronic inflammatory response characterized by elevated inflammatory cytokines, circulating monocytes, neutrophils, and T and B lymphocytes secreting autoantibodies that activate the angiotensin II type I receptor (AT1-AA). Although the pathophysiology of pre-eclampsia is becoming more defined, the genesis of the disease is still largely unknown. Furthermore, the only treatment for extreme forms of the disease is bed rest and administration of magnesium sulfate to sustain the pregnancy a few days prior to early delivery of the fetus, which can lead to devastating neurological and physical effects for the newborn. Administration of magnesium sulfate is routinely given without adverse effects. The focus of this review is to discuss the cascade of events leading to cytokines, specifically interleukin-6 (IL-6), in stimulating vasoactive substances such as AT1-AA (Figure 1) and to examine the mechanism whereby administration of magnesium sulfate can be beneficial during pre-eclampsia. One area is to decrease vascular resistance index parameters determined by Doppler velocimetry. Another potential area of benefit with magnesium sulfate administration may be to decrease inflammatory responses or decrease cardiovascular mechanisms stimulated by overexpression of inflammatory cytokines in response to placental ischemia or animal models of elevated IL-6 during pregnancy. Further studies identifying IL-6-driven mechanisms playing a role in the development of hypertension during pregnancy and how administration of magnesium sulfate can suppress them are critical to improve decisions affecting patient care in women with pre-eclampsia. The results of these types of studies will be advantageous to further our knowledge of the pathophysiological ramifications associated with pre-eclampsia and to further therapeutic development for this disease.